PARAMETRIC 3D MODELING OF I-SHAPE KITCHEN - Petar PEJIC; Dimitrije JOVANOVIC; Jovan MARINKOVIC; Vesna STOJAKOVIC; Sonja KRASIC (Journal of Industrial Design and Engineering Graphics, 2019)
Interior design is the science and art of enhancing the interior of a space in order to achieve a more aesthetically pleasing and functional environment. Furniture as an important element of space decoration can be ready-made or custom-made (goal - maximal use of space). Kitchen design requires many elements disposition rules to be respected in order to get functional space. Therefor interior designer has to spend time on solving this functionality problems and have less time for creative aesthetic work. We developed an algorithm for automatic I-shape kitchen organization on the basis of available kitchen dimensions. This algorithm automatically generates kitchen disposition and makes a parametric 3D model. Developed algorithm is implemented and tested using SketchUp dynamic components.